Exploring Al, Mn and Fe phytoextraction in 27 ferruginous rocky outcrops plant species - Schettini, Antonella T.; Leite, Mariangela G.P.; Messias, Maria Cristina T.B.; Gauthier, Arnaud; Li, Haixiao; Kozovits, Alessandra R. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2018)
•Soil Al, Fe and Mn concentrations exceed legislation toxic limits.•Metal accumulation vary widely among species and is not related to soil concentrations.•Metal hyperaccumulator plants may be not relevant for ecological restoration.•Functional plant diversity creates different opportunities to cover post-mining areas. Worldwide, substrates naturally rich in Al, Fe and Mn are the subject of mining, generating degradation of large areas and producing wastes with high pollution potential for water resources, soil and atmosphere, causing harm to human health and ecosystems. The present study investigated the total and phytoavailable concentration of these elements in soils and leaves of 27 native plant species from ferruginous rocky outcrops, finding values above the toxic limits described in literature and environmental legislation. Foliar levels of metals varied widely among species, demonstrating different phytoextraction or exclusion potentials, which were not explained by the total concentration of elements or available soil fractions. Although most species are not considered hyperaccumulators, the results indicate the existence of species related to sites of greater availability of certain metals or that can modify soil quality through their different phytoextraction skills, with potential future uses in decontamination, stabilization, phytomining and ecological restoration projects.